The development of the socio-cultural space of the coal-mining region as a factor of human resources retention - Kostiuk Natalia (EDP Sciences, 2021)
The article presents an analysis of the problem of human resource retention in the coal-mining region. It is emphasized that along with the factors of economic development it is advisable to take into account the socio-cultural needs and preferences of employees to ensure the preservation of human resources and the development of human capital on this basis. The article substantiates the need to rely on the actual socio-cultural needs of the subjects of professional activity when building activities for the development of the socio-cultural space of the coal-mining region. The article analyzes the implementation of strategic measures for the creation of the Siberian Cluster of Arts from the point of view of the development of the socio-cultural space of the region for the retention of human resources. The empirical part of the article is presented by the results of the study of socio-cultural needs, leisure preferences and the assessment of the attractiveness of the factors of living in Kuzbass by employees of the coal industry enterprises of the region. The sample population included 93 respondents living in the following cities: Kemerovo, Berezovskiy, Kiselevsk, Novokuznetsk, Polysaevo, and Prokopyevsk. The main method of collecting information was a survey conducted through GoogleForms. The analysis uses methods of mathematical statistics, quantitative and qualitative analysis of the results, and analysis of the significance of socio-cultural needs for the respondents.